STUDIES ON ORGANIC FARMING AND INTEGRATED NUTRIENT MANAGEMENT SYSTEM ON PERFORMANCE OF POTATO - YADAV, NITESH KUMAR; CHANDRAKAR, B.L.; SHARMA, GAURAV; URKURKAR, J.S. (Annals of Agricultural Research, 2014)
The application of 100% RDF produced significantly higher yield compared to all other treatments.Among the organic sources, 100% N (1/3rd each FYM + NC + CCR) + Azos. + NC and CCR along with Azospirillum fixed the nitrogen and increased the availability of nitrogen through FYM, neem cake and composed crop residues, as it was associated with crop